Enhancing Pre-Service Teachers' Creativity through Ethno-STEM Project-Based Learning in an Elementary Science Teaching Course - Ni Made Yeni Suranti; Nurkhaerat Alimuddin; Fitri Puji Astria; Aisa Nikmah Rahmatih (MO.RI Publishing, 2026)
This study investigated the extent to which the implementation of an Ethno-STEM Project-Based Learning model contributes to the development of pre-service teachers’ creative thinking skills in designing elementary science instruction. A quantitative pre-experimental approach employing a one-group pretest–posttest design was conducted in three classes involving pre-service teachers enrolled in an elementary science teaching course. Data were obtained using validated instruments designed to assess creative thinking skills in developing science learning designs for elementary education. The analysis revealed a notable increase in students’ creative thinking performance after participating in the learning activities. The average N-gain score reached 62.15%, indicating a moderate level of improvement. These results demonstrate that integrating local cultural contexts into STEM-oriented project-based learning provides meaningful opportunities for pre-service teachers to develop creative, contextually relevant instructional designs. The findings highlight the potential of the Ethno-STEM Project-Based Learning model as an alternative approach for strengthening creative instructional design skills in elementary science teacher education.